Digital destigmatization: How exposure to networking profiles can reduce social stereotypes. (November 2020) - Neubaum, German; Sobieraj, Sabrina; Raasch, Josefine; Riese, Julia
Abstract: Previous research on intergroup contact examined whether mediated and non-mediated interactions with outgroup members can ameliorate attitudes toward this outgroup. Today, intergroup encounters, though, can also occur in a more passive form, for instance, browsing through an outgroup member's social media profile. This study investigates the effects of passive intergroup contact via social networking services for three distinct stigmatized groups (people with physical disabilities, schizophrenia, and transgender individuals). In an experiment ( N = 1047), participants viewed a social media profile displaying a person's daily life experiences with either cues of a membership in a stigmatized group or not. Results indicated a small improvement of outgroup-related attitudes after intergroup contact. Contact effects, however, were contingent on whether participants perceived similarities with the profile owner. Findings are discussed in light of the intergroup contact hypothesis and its application to contemporary communication technologies. Highlights: Intergroup contact via SNS was investigated in an online experiment. Participants were exposed to a profile of a member of a stigmatized group. Attitudes improvements were detectable when perceived similarity was high.